Pengaruh Debit Aliran Terhadap Kinerja Pemisahan Limbah Microplastik Tersuspensi Menggunakan Hydrocyclone Dual Inlet Port - Qiram, Ikhwanul; Nughroho, Agung; C G, Hapsoro; Ramadhan, Chrismi Ananda (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2024)
The increasing concern regarding microplastic contamination in aquatic environments necessitates effective separation technologies. This study investigates the impact of flow rate on the performance of a dual-inlet hydrocyclone in separating dissolved microplastic waste. The hydrocyclone, known for its centrifugal separation capabilities, is adapted with dual inlets to enhance separation efficiency. Various flow rates were tested to determine their effect on separation performance, focusing on separation efficiency and the classification of successfully separated microplastics. Experimental results indicate that flow rate significantly influences the separation efficiency of the hydrocyclone. Higher input flow rates result in increased pressure drops, with pressure losses ranging from 98-99.59%. The output flow rates at both outlets (O1 and O2) increase proportionally with the input flow rate. The highest microplastic separation occurred at an input flow rate of 70 ml/sec, where the clean side output (O1) had a density of 1.03% with an average particle size of 98 µm. At an input flow rate of 80 ml/sec, the clean side output had a density of 1.28% with an average particle size of 51 µm. This study provides valuable insights into optimizing hydrocyclone design for environmental applications, particularly in reducing microplastic pollution